Stress, internet use, substance use and coping among adolescents, young-adults and middle-age adults amid the 'new normal' pandemic era - Shweta Singh; Nisha Mani Pandey; Manjistha Datta; Saakshi Batra (Elsevier, 2021)
Background: Globally, there is a constant state of flux amid the 'new normal' period of the COVID-19 pandemic. People try to accommodate to uncertainty, stress, and the threat of facing subsequent waves. It is crucial to explore and compare the psychological and behavioral processes of adolescents, young adults, and middle-aged adults amid such an era in a developing country like India. Aim: The present study compared the stress, internet use, substance use, and coping among adolescents, young adults, and middle-aged adults amid India's 'new normal' era. Methods: A cross-sectional design was used on an online platform. The sample included 1027 participants [ 456 adolescents; 347 young adults, and 224 middle age-adults] using PerceivedStress Scale, Internet Gaming Disorders-9, DSM-5 Self-Rated Level-1, and Brief-COPE scale. Results: Results showed moderate stress among all participants across all ages. Adolescent females perceived the highest stress (20.91, SD = 8.65); Adolescents reported higher internet use (Females: M = 3.59, S.D. = 2.44; Males: M = 3.40, S.D. = 2.30); Young and middle-aged adults Males reported significantly higher substance use (M = 1.60, S.D. = 2.96; M = 1.17, S.D. = 2.21). Maladaptive coping was used more by Young Adult Males (M = 10.83, S.D. = 4.66). Internet use was positively correlated with perceived stress (0.40) and maladaptive coping (0.40). Substance Use was also moderately positively correlated with maladaptive coping (0.38). Discussion: The study reveals significant variations in perceived stress, internet use, substance use, and coping based on gender and age variations. Adolescent females were the most affected and reported high perceived stress, whereas middle-aged adults were the least affected. Conclusion: The study provides further avenues to understand the stress and coping in different sections of society amid the 'new normal' era. It also gives an idea about resilience and identifies the sections of society which require focused interventions.